2022
DOI: 10.2478/acm-2022-0006
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Perception of Patient Safety Culture During the Covid-19 Pandemic – Results of a Pilot Study

Abstract: Introduction: The COVID-19 pandemic posed health and social threats and directly affected the quality and safe care. Many nursing students had mandatory practical training in hospitals to help the national system respond to the crisis. The investigation of nursing students’ perceptions of patient safety culture (PSC) might be beneficial in identifying safety areas that need improvement. Aim: The pilot study aimed to investigate nursing students’ perception of PSC during the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Its importance in patient safety competencies has also been emphasized by Wulandi (2020); nevertheless, clinical practice under a mentor / supervisor is rare in the Czech Republic. Similar results were achieved in Slovakia, where the evaluation of PSC during the pandemic was influenced mainly by the form of study, experience in providing nursing care, age, knowledge of any systems for adverse events reporting, the current workplace, and clinical supervision (Kalánková et al, 2022). The final aim of our paper was to examine predictors (overall level of patient safety and numbers of adverse events reported).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Its importance in patient safety competencies has also been emphasized by Wulandi (2020); nevertheless, clinical practice under a mentor / supervisor is rare in the Czech Republic. Similar results were achieved in Slovakia, where the evaluation of PSC during the pandemic was influenced mainly by the form of study, experience in providing nursing care, age, knowledge of any systems for adverse events reporting, the current workplace, and clinical supervision (Kalánková et al, 2022). The final aim of our paper was to examine predictors (overall level of patient safety and numbers of adverse events reported).…”
Section: Discussionsupporting
confidence: 56%
“…In the Czech Republic, the worst rated dimensions were Frequency of events reported (30.53%) and Staffing (38.1%) and the best were Communication openness (70.4%) and Teamwork within units (69.43%). In Slovakia, nursing students also awarded the worst scores for Frequency of events reported (33%) and Staffing (35%), while the best scores were given for Feedback & communication about error (55%) and Communication openness (53%) (Kalánková et al, 2022). In terms of factors that influence the evaluation of dimensions, previous studies before the pandemic have indicated that patient safety knowledge tends to increase over the years (Alquwez et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another pilot study reported that the overall patient safety grade, the number of reported events, and the number of reported events by nursing students were significantly predicted by several patient safety competence dimensions ( p ≤ 0.05) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%